Monitoring Water Quality Parameters in Shrimp Aquaculture - Vicknes Chan Tian Seng,; Cholan, Noran Azizan; Kim Gaik Tay, Kim Gaik; Paramalingam, Linges; Nurfatihah Che Abd Rashid, Nurfatihah Che Abd; Jaafar, Siti Farhana Mohamad; Budi Astuti, Budi; Ngajikin, Nor Hafizah (International Journal of Integrated Engineering, 2025)
In shrimp aquaculture, maintaining optimal water quality is essential for ensuring the health and growth of shrimp. This study focuses on the real-time monitoring of water quality parameters, using a multi-sensor system that measures temperature, salinity, dissolved oxygen (DO), pH, total dissolved solids (TDS), and turbidity. With the use of a solar panel for electricity, the multi-sensor system is capable in monitoring the water quality of a shrimp pond over two consecutive days. Based on the measurement data, the measured range is 6.5 – 9.0 for pH, 19 – 31.5°C for temperature, 9.0 – 25.0 ppt for salinity and 2.0 – 12.0 NTU for turbidity. The range of these parameters is ideal for shrimp aquaculture. Nevertheless, the TDS and DO do not meet the ideal range. TDS should be less than 1500 ppm, with a measured range of 1800 to 3400 ppm. Feed inputs and the buildup of metabolic waste may be the cause of this high TDS value. In the meantime, DO measures in the range of 2.5 to 22.0 ppm, with the lowest DO occurring late at night and falling below the DO limit of 5 ppm. By using mechanical aeration late at night to raise the DO level, this DO shortage can be resolved. The findings demonstrate that in order to guarantee accurate control of crucial parameters, ongoing real-time monitoring of sensor technology is required. Shrimp aquaculture may become much more sustainable and efficient by implementing automated systems for water quality regulation, which also lowers the risks related to environmental variations.